Republic of Serbia : Ex Post Assessment of Longer-Term Program Engagement and Ex Post Evaluation of Exceptional Access: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Republic of Serbia. (IMF Staff Country Reports; Country Report, 2011)
Serbia has undergone a significant transformation, going from post-conflict devastation to being a legitimate aspirant to EU accession status. An IMF-supported program helped the country navigate the global financial crisis, and recovery is in train. Economic institutions have improved, in particular with the establishment of the fiscal responsibility law, the adoption of inflation targeting, and strengthening of banking supervision and regulation. But despite these successes, substantial vulnerabilities and a large structural reform agenda have to be taken up to continue progress.